2016
DOI: 10.1111/jvim.13918
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cobalamin and Methylmalonic Acid Concentrations in Hyperthyroid Cats Before and After Radioiodine Treatment

Abstract: BackgroundHyperthyroidism, the most common endocrine disorder in cats, has been associated with low serum cobalamin concentrations. Whether this is a functional cobalamin deficiency of clinical importance has not been assessed.Hypothesis/ObjectivesCats with hyperthyroidism experience a functional cobalamin deficiency which correlates with their clinical catabolic state and is reversible with return of the euthyroid state.AnimalsThirty‐nine client‐owned hyperthyroid cats.MethodsProspective observational study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
12
1
2
Order By: Relevance
“…It has recently been shown that hypocobalaminemia in cats with hyperthyroidism, in which underlying gastrointestinal disease is unlikely, is not a functional deficiency requiring supplementation . In contrast, all four hyperthyroid cats in the present study also had biochemical evidence of Cbl deficiency.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…It has recently been shown that hypocobalaminemia in cats with hyperthyroidism, in which underlying gastrointestinal disease is unlikely, is not a functional deficiency requiring supplementation . In contrast, all four hyperthyroid cats in the present study also had biochemical evidence of Cbl deficiency.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, all four hyperthyroid cats in the present study also had biochemical evidence of Cbl deficiency. This difference probably is a reflection of variances in inclusion criteria; we deliberately aimed to select cats with gastrointestinal disease, whereas the other study excluded cats suspected of having or diagnosed with gastrointestinal disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diese kann mit niedrigen Cobalaminkonzentrationen im Serum einhergehen (Prävalenz ca. 40%) 24 . Allerdings handelt es sich bei hypocobalaminämischen Katzen mit unbehandelter Hyperthyreose, sofern nicht gleichzeitig eine chronische gastrointestinale Erkrankung oder EPI vorliegt, nicht um einen funktionellen Cobalaminmangel (d. h. auf zellulärer Ebene) und verlangt daher nicht zwangsläufig eine Supplementation 24 .…”
Section: Hyperthyreoseunclassified
“…1,7 In addition to typical disease associations, some authors have suggested that feline cardiomyopathy, arterial thromboembolism and hyperthyroidism are associated with decreased serum cobalamin concentrations; 8,9 although a recent study found that the prevalence of hypocobalaminaemia in hyperthyroid cats was low, while folate was significantly lower in hyperthyroid cats compared with when the same cats were euthyroid post-radioiodine treatment. 10 Lastly, congenital abnormalities impeding cobalamin absorption have been reported, albeit rarely, in cats. 11,12 Factors other than disease have been found to have an effect on cobalamin and folate serum concentrations.…”
Section: Introductionmentioning
confidence: 99%